Multiple host switching events shape the evolution of symbiotic palaemonid shrimps (Crustacea: Decapoda) - Horká, Ivona; De Grave, Sammy; Fransen, Charles H J M; Petrusek, Adam; Ďuriš, Zdeněk (Scientific reports, 2016)
The majority of the almost 1,000 species of Palaemonidae, the most speciose family of caridean shrimp, largely live in symbioses with marine invertebrates of different phyla. These associations range from weak epibiosis to obligatory endosymbiosis and from restricted commensalism to semi-parasitism, with the specialisation to particular hosts likely playing a role in the diversification of this shrimp group. Our study elucidates the evolutionary history of symbiotic palaemonids based on a phylogenetic analysis of 87 species belonging to 43 genera from the Indo-West Pacific and the Atlantic using two nuclear and two mitochondrial markers. A complementary three-marker analysis including taxa from GenBank raises this number to 107 species from 48 genera. Seven larger clades were recovered in the molecular phylogeny; the basal-most one includes mostly free-living shrimp, albeit with a few symbiotic species. Ancestral state reconstruction revealed that free-living forms likely colonised cnidarian hosts initially, and switching between different host phyla occurred multiple times in palaemonid evolutionary history. In some cases this was likely facilitated by the availability of analogous microhabitats in unrelated but morphologically similar host groups. Host switching and adaptations to newly colonised host groups must have played an important role in the evolution of this diverse shrimp group.
Keywords: Sequence Analysis, DNA; Animals; Host Specificity; molekulární evoluce; Phylogeny; symbióza; genetické markery; zvířata; Palaemonidae; sekvenční analýza DNA; fylogeneze; Symbiosis; DNA, Mitochondrial; Evolution, Molecular; mitochondriální DNA; hostitelská specificita; Genetic Markers